2021
DOI: 10.1097/nmd.0000000000001386
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Social Support, and Death Anxiety in Patients With Chronic Kidney Failure

Abstract: Purpose: This study aimed to investigate the relationship between mental health, perceived social support, and death anxiety, and the predictive roles of mental health and perceived social support in the explanation of death anxiety in a sample of adults with chronic kidney disease. Methods: A demographic questionnaire, the Symptom Check List−25, the Social Support Survey Scale, and the Death Anxiety Scale (DAS) were used in the present study. The sample consisted of 58 adult patients with chronic kidney failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
(140 reference statements)
1
2
0
Order By: Relevance
“…Finally, older adults living with a life-threatening disease and having a history of psychiatric disorders had higher death anxiety levels and lower self-transcendence levels. These results are in accord with recent studies (Brown et al, 2014; Guner et al, 2023; Khodarahimi et al, 2021), indicating that older people with a disease that threatens their lives tend to worry about dying. In contrast to earlier findings (Ho et al, 2016), people who are free of potentially fatal diseases or psychiatric disorders reported higher scores in self-transcendence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, older adults living with a life-threatening disease and having a history of psychiatric disorders had higher death anxiety levels and lower self-transcendence levels. These results are in accord with recent studies (Brown et al, 2014; Guner et al, 2023; Khodarahimi et al, 2021), indicating that older people with a disease that threatens their lives tend to worry about dying. In contrast to earlier findings (Ho et al, 2016), people who are free of potentially fatal diseases or psychiatric disorders reported higher scores in self-transcendence.…”
Section: Discussionsupporting
confidence: 92%
“…Death anxiety has been studied in many mental disorders, such as somatic symptom disorders, anxiety disorders, obsessive-compulsive disorders, and post-traumatic stress disorder (PTSD; Abbas et al, 2021; Iverach et al, 2014; Khodarahimi et al, 2021; Mavrogiorgou et al, 2020). These studies have shown a positive relationship between mental health history and death anxiety.…”
Section: Death Anxietymentioning
confidence: 99%
“…The frequency and intensity of thoughts about death increase in chronic diseases (Francalancia et al, 2021;Khawar et al, 2013;Khodarahimi et al, 2021). Some studies have shown that patients with chronic diseases have more significant death anxiety than healthy controls (Strömberg & Jaarsma, 2008).…”
Section: Discussionmentioning
confidence: 99%